2018
DOI: 10.1177/0020872818788397
|View full text |Cite
|
Sign up to set email alerts
|

Environmental social work in the disciplinary literature, 1991–2015

Abstract: Despite increasing acknowledgment that the social work profession must address environmental concerns, relatively little is known about the state of scholarship on environmental social work. This study provides a scientometric summary of peer-reviewed articles ( N = 497) pertaining to environmental topics in social work journals between 1991 and 2015. We find that theoretical and empirical scholarship on environmental social work is growing, though this growth remains limited to specific geographical regions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 20 publications
3
39
0
3
Order By: Relevance
“…In this way, ecosocial work can be understood as a form of anti-oppressive social work (Dominelli, 2002) that also is consistent with the values and principles of the environmental justice movement (Bryant, 1995;Bullard, 1996) and critical youth empowerment (Jennings et al, 2006). Although social work research has examined interventions that can mitigate harm caused by environmental crises and natural disasters (Krings, Victor, Mathias, & Perron, 2018b;Mason, Shires, Arwood, & Borst, 2017), additional research is needed to develop methods that proactively engage people in critical reflection and action relating to their self-determination, health, and natural and built environments. In particular, youth of color living in communities with high levels of poverty, who are disproportionately impacted by environmental hazards (Evans, 2004), merit a seat at decision making tables relating to their communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, ecosocial work can be understood as a form of anti-oppressive social work (Dominelli, 2002) that also is consistent with the values and principles of the environmental justice movement (Bryant, 1995;Bullard, 1996) and critical youth empowerment (Jennings et al, 2006). Although social work research has examined interventions that can mitigate harm caused by environmental crises and natural disasters (Krings, Victor, Mathias, & Perron, 2018b;Mason, Shires, Arwood, & Borst, 2017), additional research is needed to develop methods that proactively engage people in critical reflection and action relating to their self-determination, health, and natural and built environments. In particular, youth of color living in communities with high levels of poverty, who are disproportionately impacted by environmental hazards (Evans, 2004), merit a seat at decision making tables relating to their communities.…”
Section: Discussionmentioning
confidence: 99%
“…Yet the perceptions of youth activists, and the role of youth participation within ecosocial work broadly, have received limited attention to date. A comprehensive review of social work literature addressing environmental topics found no title nor abstract including the words "youth," "young people," or "children" (Krings, Victor, Mathias, & Perron, 2018a).…”
Section: Integrating Youth Participation and Ecosocial Work: New Possmentioning
confidence: 99%
“…Scholarship relating to environmental social work is growing (Krings, Victor, Mathias, & Perron, 2018; Mason, Shires, Arwood, & Borst, 2017), and social work researchers have made important contributions to the first and second waves of environmental justice organizing. This innovative work has examined important issues relating to the application of environmental justice principles to social work practice (Dominelli, 2013; Hawkins, 2010; Hoff & Rogge, 1996) and education (Miller et al, 2012; Philip & Reisch, 2015; Teixeira & Krings, 2015); procedural justice concerns relating to environmental decision making (Rambaree, 2013); distributional justice issues, such as reducing exposure to toxins and contamination (Rogge & Combs‐Orme, 2003) and equitably providing environmental goods and services relating to food justice (Besthorn, 2013), and clean water (Akdim, El Harchaoui, Laaouan, & Soydan, 2012; Case, 2017; Mitchell, 2018; Singh & Singh, 2015; Willett, 2015).…”
Section: Environmental Justice Organizing and Social Workmentioning
confidence: 99%
“…Social work research that includes environmental sustainability has already claimed a remarkable space as an emerging area in the discipline, as seen in literature reviews (Krings, Bryan, Victor, Mathias, & Perron, 2018;Nöjd, 2017;Ramsay & Boddy, 2017). Several authors have even begun to use the concept of ecosocial work to describe this area (Bailey, Hendrick, & Palmer, 2018;Boetto, 2017;Crews & Besthorn, 2016).…”
Section: Context: Social Work Research On An Environmentally Sustainamentioning
confidence: 99%